2021
DOI: 10.30973/aap/2021.7.0071007
|View full text |Cite
|
Sign up to set email alerts
|

Processing effect on the bioactive compounds content of Mexican jalapeño peppers for chipotle (Capsicum annum L.)

Abstract: The objective of this work was to evaluate the antioxidant capacity and bioactive compounds content in two Jalapeño pepper varieties, both fresh and smoked-dehydrated (chipotle) and in commercial chipotle pepper sauces. The antioxidant capacity, capsaicin content, carotenoids and total phenols were evaluated. The smoked-dehydrated process had an effect on all the variables analysed (P?0.05). The chipotle pepper presented higher antioxidant activity (112.33 µmol ET/g) and content of bioactive compounds than fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Diversas investigaciones han demostrado que la aplicación de Se, puede incrementar la producción de compuestos bioactivos (Motesharezadeh et al, 2020). Resultados similares a los del presente estudio fueron obtenidos en Capsicum annuum L., donde la aplicación de Se incrementó diversos compuestos bioactivos como fenoles, flavonoides y capacidad antioxidante (Natividad-Torres et al, 2021). Esta capacidad bioactiva posiblemente sea atribuida a la acción sinérgica que tiene el Se al poder actuar como un elemento vital al alterar varios procesos fisiológicos y bioquímicos D'Amato et al…”
Section: Compuestos Bioactivosunclassified
See 1 more Smart Citation
“…Diversas investigaciones han demostrado que la aplicación de Se, puede incrementar la producción de compuestos bioactivos (Motesharezadeh et al, 2020). Resultados similares a los del presente estudio fueron obtenidos en Capsicum annuum L., donde la aplicación de Se incrementó diversos compuestos bioactivos como fenoles, flavonoides y capacidad antioxidante (Natividad-Torres et al, 2021). Esta capacidad bioactiva posiblemente sea atribuida a la acción sinérgica que tiene el Se al poder actuar como un elemento vital al alterar varios procesos fisiológicos y bioquímicos D'Amato et al…”
Section: Compuestos Bioactivosunclassified
“…Por otro lado, el chile jalapeño (Capsicum annuum L.), una de las plantas más cultivadas en el mundo, debido a su importancia en la nutrición humana como en la industria farmacéutica (Espinosa-Palomeque et al, 2020), los frutos de son una fuente de vitaminas. (A, E y C), carotenoides, capsaicinoides y compuestos fenólicos con propiedades antioxidantes para la dieta humana (Natividad-Torres et al, 2021).…”
Section: Introductionunclassified
“…Some of the chemical compounds found in them are guaiacol, formaldehyde, formic acid, acetone, short chain fatty acids, methanol, ethanol, furfural, acetaldehydes and volatile phenolic compounds [ 39 ]. In addition, it has been found that chipotle peppers have a higher antioxidant activity and content of bioactive compounds (phenols and carotenoids) than fresh peppers [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%